Textile Antenna with Meta-Surface on Curved-Surface for Smart Clothing Applications - Worathan Wichakoon; Praphat Arnmanee; Pitchanun Wongsiritorn; Chuwong Phongcharoenpanich (My University, 2025)
This paper presents a textile antenna integrated with a meta-surface for smart clothing applications, designed for installation on curved surfaces. The antenna is designed to operate over a wide frequency band, including the 2.4 GHz band, making it suitable for wearable applications. Its structure comprises a textile antenna and a 3×3 meta-surface array, fabricated using felt and Shieldit fabric. The antenna demonstrates key characteristics such as adaptability to curved surfaces, reduced specific absorption rate (SAR), and high gain. Experimental results indicate that when installed on a curved surface, the |S11| parameter remains below -10 dB at 2.4 GHz, with an antenna gain ranging from 4.62 to 6.71 dBi. The antenna is evaluated at three positions on clothing—chest, shoulders, and back—exhibiting consistent performance in terms of |S11|, gain, and radiation pattern.
Keywords: Advanced Antenna and Metasurface Technologies; Antenna Design and Analysis; Advanced Materials and Mechanics